M. P. Irigoyen Troconis, (comp.), La universidad novohispana. Voces y enseñanzas clásicas, México D.F., UNAM, 2003, 151 pp. (Minerva. Revista de Filología Clásica, 2019)
Reseña de M. P. Irigoyen Troconis, (comp.), La universidad novohispana. Voces y enseñanzas clásicas, México D.F., UNAM, 2003, 151 pp.